Demonstration of T-Cell Monotypia Using Anti-TCRbeta1/2 (TRBC1/2) Immunostaining as a Rapid and Cost-Effective Alternative to PCR-Based Clonality Studies for the Diagnosis of T-Cell Lymphoma - Elizabeth J. Soilleux; Daniel T. Rodgers; Jinlong J. Situ; Shelley C. Evans; Venkata N. Konda; Han-Chieh Yang; Jianxiong Pang; Isabella Gilbey Smith; Pete Rajesh; Maryam Salimi; Soo Weei Ng; Julia Jones; et al. (Diagnostics)
Background/Objectives: T-cell lymphomas are often histologically indistinguishable from benign T-cell infiltrates, and diagnosis typically relies on slow, complex, and expensive multiplexed PCR reactions, requiring significant training and experience to interpret them. We aimed to raise highly specific antibodies against the two alternatively used and very similar T-cell receptor beta constant regions, TCRbeta1 and TCRbeta2, encoded by the TRBC1 and TRBC2 gene segments, respectively. We sought to demonstrate the feasibility of detecting TCRbeta1 and TCRbeta2 immunohistochemically in routine clinical (formalin-fixed, paraffin-embedded (FFPE)) tissue sections as a novel diagnostic strategy for T-cell lymphomas. Methods: Recombinant rabbit antibodies were validated using Western blotting and FFPE immunostaining of T-cell leukemia lines. The immunostaining of FFPE tissue containing benign and lymphomatous T-cell populations was undertaken, with corroboration by BaseScopeTM high-sensitivity in situ hybridization and quantitative real-time PCR (Q-PCR). An additional Q-PCR literature review and analysis of publicly available RNAseq data was used to determine the TCRbeta2/TCRbeta1 ratio cut-off to separate benign and malignant T-cell populations. Results: Our TCRbeta1/TCRbeta2 antibody pair gave highly specific FFPE tissue staining. All benign samples analyzed (immunohistochemically, by BaseScopeTM, by Q-PCR, and by RNAseq data analysis) had TCRbeta1/TCRbeta2 or TRBC1/TRBC2 ranges well within the previously published flow cytometric benign range (TCRbeta2/TCRbeta1 = 0.18:1–5.7:1), while samples of T-cell lymphoma did not. One out of thirteen (7.7%) lymphoma samples showed some detectable TCRbeta1/TCRbeta2 protein co-expression, and 4 out of 13 (30.8%) T-cell lymphomas showed a TRBC1/TRBC2 transcript co-expression using BaseScopeTM. Conclusions: Analyzing T-cell monotypia immunohistochemically, analogous to B-cell monotypia (kappa: lambda ratio for B-cell and plasma cell neoplasms), could make the diagnosis of T-cell lymphomas cheaper, quicker, and more accurate. Larger studies are needed to validate our antibodies for clinical use.